Improving the Efficiency of MSME Financial Statements through Microsoft Excel-Based Applications - Derry Nugraha; Fazrian Thursina; Anjani; Putri Devina; Ade Irma; Neli Deti (Westscience Press, 2023)
This article discusses the use of Microsoft Excel application to improve the efficiency of financial statements in Micro, Small and Medium Enterprises (MSMEs). The purpose of this study is to evaluate the effectiveness of using Excel applications in preparing MSME financial statements, as well as to identify benefits and constraints that may arise in the use of this application. The research method used is a case study by collecting data through interviews and observations of MSMEs that use Excel applications in preparing financial statements. The results showed that the use of Excel applications can increase the efficiency of preparing MSME financial statements. This application allows MSMEs to easily organize and manage their financial data, perform automatic calculations, and present financial information in a more accurate and structured manner. In addition, the use of Excel applications also speeds up the process of preparing financial statements and minimizes human error. In conclusion, the use of Microsoft Excel application can increase the efficiency of preparing MSME financial statements. This application allows MSMEs to manage financial data more efficiently, perform automatic calculations, and present financial information accurately. However, it should be noted that the use of the Excel application also requires adequate user understanding and skills. Therefore, training and mentoring in the use of this application is highly recommended to maximize its benefits for MSMEs.